Prevalence and Progression of Pigment Clumping Associated with Idiopathic Macular Telangiectasia Type 2 (IMT2) - Meleth, Annal D. (2013)
PURPOSE: To investigate pigment clumping in idiopathic macular telangiectasia type 2 (IMT2) for its incidence, development, and progression during the course of the disease. METHODS: Patients with a diagnosis of IMT2 and greater than 12 months of follow-up were reviewed retrospectively. Measurements of the area of pigment clumping were performed and correlated with visual acuity and findings on spectral domain optical coherence tomography (OCT) and microperimetry (MP1). RESULTS: Fifty-three eyes in 27 patients with a mean follow-up of 42.5±14.2 months (range 12–79 months) were included. At study baseline, 16 eyes (30%) had evidence of pigment clumping without associated neovascular changes. During follow-up, 8/33 (24%) additional study eyes without prior pigment clumping developed it in stage 3 (Gass-Blodi classification) disease. Pigment clumping increased in overall area as a function of follow-up time. Pigment clumping was associated with increased intraretinal reflectivity on OCT and development of scotomas on microperimetry. CONCLUSIONS: Pigment clumping commonly develops in stage 3 IMT2 disease, enlarges in area continuously over time, and is associated with declining visual function. Longitudinal measurements of the total area of pigment clumping may be helpful in following disease progression and may constitute a useful outcome measure for interventional clinical studies.